2017
DOI: 10.1016/j.bioelechem.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of anaerobic lysine production in Corynebacterium glutamicum electrofermentations

Abstract: It has been suggested that application of electric potential can affect lysine producing fermentations, although experimental evidence is lacking. To study this hypothesis we used the lysine producer Corynebacterium glutamicum ZW04, and we exposed it to 12 different conditions regarding anaerobic gas environment, applied electrode potential (cathodic, open circuit, anodic), redox mediator and nitrate presence. The gas environment was found to play a major role, with CO leading to double the lysine concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…On the other hand, under oxidative conditions its redox potential is too negative to allow acceptance of electrons from the terminal components of the cellular electron transport chain of C. glutamicum (Kracke et al, ). Interestingly lysine concentrations and yields observed by us were comparable to those reported in the same study but under reductive conditions (Xafenias et al, ), in spite of the fact that in that study a further optimized production strain was used. This strain carried two additional beneficial mutations for lysine production (Ohnishi et al, ), yet no better outcome was achieved.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…On the other hand, under oxidative conditions its redox potential is too negative to allow acceptance of electrons from the terminal components of the cellular electron transport chain of C. glutamicum (Kracke et al, ). Interestingly lysine concentrations and yields observed by us were comparable to those reported in the same study but under reductive conditions (Xafenias et al, ), in spite of the fact that in that study a further optimized production strain was used. This strain carried two additional beneficial mutations for lysine production (Ohnishi et al, ), yet no better outcome was achieved.…”
Section: Discussionsupporting
confidence: 88%
“…Xafenias et al () recently tested anthraquinone‐2‐sulfonate (AQ2S) as a mediator to increase the production of lysine under oxidative and reductive conditions in a BES. In contrast to our study, no growth could be observed but different effects on different metabolic products were described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. glutamicum, an important Gram-positive industrial bacterium, can utilize oxygen as a preferable terminal electron acceptor in its respiratory system [7][8][9]. Manipulation of the redox metabolism of C. glutamicum connected with a cathode in a bioelectrochemical reactor system resulted in higher yields of the target product (l-lysine) when supplemented with AQDS [10]. Such results suggest that direct electron transfer between C. glutamicum and an electrode might be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have been carried out to examine electron transfer or utilization in BES with suspended microorganisms (Harnisch, Rosa, Kracke, Virdis, & Krömer, ), mostly in classic BES, such as the popular H‐cell reactors, which are hardly applicable for industrial bioprocesses and have inherent shortcomings for the control of culture conditions and quantification of electron transfer (Utesch & Zeng, ). Indirect electron transfer via mediators in suspension culture is an alternative process, where even none‐electroactive microorganisms can be influenced for enhanced production of valuable products (Aulenta, Di Maio, Ferri, & Majone, ; Choi, Um, & Sang, ; Xafenias, Kmezik, & Mapelli, ). Kracke, Virdis, Bernhardt, Rabaey, and Krömer () first reported a metabolic shift in Clostridium autoethanogenum towards more reduced products because of the electron supply in BES dependent on the redox potentials (RPs) of utilized mediators and intracellular electron acceptors (Kracke et al, ).…”
Section: Introductionmentioning
confidence: 99%